2011
DOI: 10.1051/0004-6361/201117522
|View full text |Cite
|
Sign up to set email alerts
|

The red-sequence of 72 WINGS local galaxy clusters

Abstract: We study the color−magnitude red sequence and blue fraction of 72 X-ray selected galaxy clusters at z = 0.04−0.07 from the WINGS survey, searching for correlations between the characteristics of the red sequence (RS) and the environment. We consider the slope and scatter of the red sequence, the number ratio of red luminous-to-faint galaxies, the blue fraction, and the fractions of ellipticals, S0s, and spirals that compose the RS. None of these quantities correlate with the cluster velocity dispersion, X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 84 publications
(126 reference statements)
15
33
1
Order By: Relevance
“…Our results indicate that pre-processing in groups leads to a strong evolution in galaxy properties, before they are accreted by large clusters. In agreement to Valentinuzzi et al (2011), we find that local density is the main driver for galaxy evolution and not the parent halo mass. The evolution is such that star formation is quenched in the group scale, but morphological transformation is a separate process, occurring in larger galaxy systems.…”
Section: Transitional Galaxy Populations: Blue Bulges and Red Discssupporting
confidence: 87%
“…Our results indicate that pre-processing in groups leads to a strong evolution in galaxy properties, before they are accreted by large clusters. In agreement to Valentinuzzi et al (2011), we find that local density is the main driver for galaxy evolution and not the parent halo mass. The evolution is such that star formation is quenched in the group scale, but morphological transformation is a separate process, occurring in larger galaxy systems.…”
Section: Transitional Galaxy Populations: Blue Bulges and Red Discssupporting
confidence: 87%
“…Popesso et al found significant suppression in the late type luminosity function (corresponding to our blue population) for small cluster-centric distances; we find that there is substantial change in the red luminosity function close to the cluster core as well. The colour-magnitude relation parameters drawn from the WINGS clusters (Valentinuzzi et al 2011) are quite similar to the values we see here, although the gradient scatter from our sample is twice as large as that from WINGS. That sample is also X-ray selected, but from clusters with lower Table 1.…”
Section: Discussionsupporting
confidence: 81%
“…Bower, Lucey & Ellis 1992;Valentinuzzi et al 2011). The origin of the red sequence and its relation to the massmetallicity relation was explored in a seminal paper by Arimoto & Yoshii (1987).…”
Section: Red Sequence Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We started by comparing the color-magnitude (CM) relation (B − V)(≤ r) − M V of clusters with the average red sequence slope found by Valentinuzzi et al (2011) for the WINGS galaxies in the CM diagrams of the single clusters. In Figure 10 …”
Section: Color-magnitude Diagram Of Galaxy Clustersmentioning
confidence: 99%